The Development of News Based Bioconservation Teaching Material Supplements to Embedding Environmental Awareness (Universitas Negeri Semarang, 2020)
Teaching material supplement of News based bioconservation is compiled based on environmental news in the newspapaer in North Maluku. This study has purpose to identify the feasibility, readability and effectiveness of the news based bioconservation teaching material supplements. This study applied a Research and Development (R&D) approach. The subjects in this study were the fifth grade students of SD Inpres Aru Irian and SD BPD Falila, Morotai Island Regency. The data collection technique was carried out using expert validation questionnaires, student response questionnaires and cognitive tests. The data obtained by expert validation showed a score of 90.79%, indicated that the news based bioconservation teaching material supplement was very suitable to be used in the learning. The effectiveness of teaching material supplements was determined based on the classical completeness and N-gain values. The classical completeness of students in the pretest test was 29%, meanwhile, in the posttest test was 86%. Based on the classical completeness requirements â‰¥80%, indicated that students completed classically. The N-gain test obtained was 0.75 with high criteria or classified g â‰¥ 0.7, it was concluded that the teaching material supplement of news based bioconservation teaching was effective in improving student learning outcomes. The understanding of environmental awareness was obtained using an environmental awareness questionnaire, the criteria obtained were high with a mean score of 73.88%. Based on the result of the study, then, it can be concluded that teaching material supplement of news based bioconservation is appropriate to be used as teaching materials in the learning and effectively embedding the student learning outcomes and the understanding of environmental awareness.